LncRNA HCG11 Facilitates Nasopharyngeal Carcinoma Progression Through Regulating miRNA-490-3p/MAP3K9 Axis - Zheng, Jian; Zhao, Zhuochen; Ren, Huijun; Wang, Yongfeng; Meng, Xianchun; Zhang, Wenjing; Zhang, Cai; Ming, Liang; Lu, Xiubo (Frontiers in Oncology, 2022)
Purpose Long noncoding RNAs (LncRNAs) play complex but important roles in the progression of various tumors. This study aimed to elucidate the functional mechanisms of the HLA complex group 11 (HCG11) in nasopharyngeal carcinoma (NPC). Patients and Methods HCG11 levels in NPC specimens were determined by fluorescence in situ hybridization (FISH) and qPCR. Proliferation, apoptosis, and metastasis of NPC cells were determined using CCK8, colony formation, annexin V-PI, and transwell assays. A murine tumor xenograft model was used to investigate the regulatory function of HCG11 in NPC in vivo, and immunohistochemical staining was used to determine the Ki-67 level in tumors. The target relationships between HCG11, microRNA miR-490-3p, and MAPK kinase kinase 9 (MAP3K9) were detected using bioinformatics, qPCR, western blotting, and luciferase reporter assays. Results HCG11 was highly expressed in NPC tissues and was positively associated with tumor stage, lymphatic metastasis, and poor prognosis. Functionally, HCG11 knockdown inhibited proliferation and migration and induced apoptosis of NPC cells. Mechanistically, miR-490-3p is a direct target of HCG11, oncogenic functions of HCG11 in NPC cell proliferation and migration can be partially reversed by the miR-490-3p inhibitor. HCG11 significantly increased mitogen-activated protein kinase MAPK kinase 9 (MAP3K9) levels by inhibiting miR-490-3p. Conclusion HCG11 facilitates NPC progression via MAP3K9 signaling by sponging miRNA-490-3p, which may contribute to new prognostic markers and promising therapeutic targets.